1974
DOI: 10.1021/jm00254a019
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical aspects and metabolite formation in the in vivo metabolism of the psychotomimetic amine, 1-(2,5-dimethoxy-4-methylphenyl)-2-aminopropane

Abstract: Our interest in structure-metabolism relationships of pharmacologically active l-phenyl-2-aminopropanes has led to in vivo investigations of the fate of the psychotomimetic amine l-(2,5-dimethoxy-4-methylphenyl)-2-aminopropane (1). Compound 1 was resolved via its o-nitrotartranilate salts and the absolute configurations were found to be (S)-( + ) and (fi)-(-). Determination of the enantiomeric composition of unmetabolized amine excreted in the urine of rabbits treated with racemic 1 established the R/S ratio t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…For the rat drug discrimination studies, (±)-1-(2,5-dimethoxy 4-methylphenyl)-2-aminopropane hydrochloride (DOM) was a gift from NIDA, NIH (Bethesda, MD); R -DOI HCl and 5-OMe DMT hydrogen oxalate were synthesized at VCU (Richmond, VA). For the monkey drug discrimination studies DOM was synthesized at Alcon by reported procedures (Matin et al, 1974;Shulgin, 1970) and ( R )-(+)-α-(2,3-dimethoxyphenyl)-1-[2-(4-fluorophenyl)ethyl]-4-piperidinemethanol (MDL 100907) was synthesized at the Laboratory of Medicinal Chemistry, NIDDK, NIH (Bethesda, MD) as previously described (Ullrich and Rice, 2000). MDL 100907 was dissolved in 20% aqueous dimethyl sulfoxide (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…For the rat drug discrimination studies, (±)-1-(2,5-dimethoxy 4-methylphenyl)-2-aminopropane hydrochloride (DOM) was a gift from NIDA, NIH (Bethesda, MD); R -DOI HCl and 5-OMe DMT hydrogen oxalate were synthesized at VCU (Richmond, VA). For the monkey drug discrimination studies DOM was synthesized at Alcon by reported procedures (Matin et al, 1974;Shulgin, 1970) and ( R )-(+)-α-(2,3-dimethoxyphenyl)-1-[2-(4-fluorophenyl)ethyl]-4-piperidinemethanol (MDL 100907) was synthesized at the Laboratory of Medicinal Chemistry, NIDDK, NIH (Bethesda, MD) as previously described (Ullrich and Rice, 2000). MDL 100907 was dissolved in 20% aqueous dimethyl sulfoxide (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…To a solution of 3-bromo-4,5-dihydroxybenzaldehyde 7 (1.10 g, 5.1 mmol) in DMSO (3.6 ml) was added methylene iodide (0.87 ml, 10.8 mmol) followed by anhydrous potassium carbonate (2.00 g), which was heated at 1008C for 3 h. After it had returned to room temperature, it was added to water (100 ml), made strongly basic by the addition of sodium hydroxide, and extracted using dichloromethane. These extracts were dried over anhydrous sodium Synthesis of 3-hydroxyl-4,5-methyenedioxybenzaldehyde (11). A mixture of 3-bromo-4,5-methylenedioxybenzaldehyde 8 (1.30 g, 5.7 mmol), cyclohexylamine (2.2 ml, 19 mmol) and toluene (10 ml) was refluxed in a Dean-Stark apparatus for 3.5 h. After cooling, the excess solvent was removed using a rotary evaporator, and thoroughly dried in vacuum, producing 3-bromo-4,5-methylenedioxybenzylidine-N-cyclohexylamine 9 (1.50 g, 4.8 mmol) in a yield of 86%.…”
Section: Synthesis Of 3-bromo-45-dihydroxy-benzaldehyde (7)mentioning
confidence: 99%
“…When an aliphatic chain is attached to an aromatic ring, the resulting benzylic position becomes prone to hydroxylation by mammalian (152) and microbial (153) systems. Substrates typically hydroxylated by mammals a t aliphatic carbons include n-propylbenzene (XVIII) (152), the psychotomimetic 1-(2,5-dimethoxy-4-rnethylphenyl)-2-aminopropane (XIX) (154), and tolbutamide (XX) (155,156) Cora converts the steroidal thioether (XVII) into its optically active sulfoxide (134). N-Oxidations-Since the N-oxidation products of numerous therapeutic agents possess enhanced toxicities, there is considerable interest in this biotransformation (135,136).…”
Section: Scheme Zvmentioning
confidence: 99%